Biblical „grumble” - Bogdan Zbroja (Ruch Biblijny i Liturgiczny, 2005)
The human grumble is a common situation in various biblical chapters. There are more than fifty places, which mention such a talk. Not always it refers to objection to God; the people grumble at each other, too. The article above depicts every Bible’s text, which develops this theme. The basis cause of such a behavior, as it can be concluded from the analysis, is a dissatisfaction with one’s own life, with one’s own fate. Sometimes the people grumble because of disagreement with prophet’s call or demands. Such an attitude is observed also during Church’s history. The elaboration makes it possible to discover a specific of this human behavior, whose roots are present already in the Book of Exodus.